Green Brand Innovation Dan Green Brand Loyalty: Peran Mediasi Green Perceived Value - Lesmana, Shindu; Fikri, Muhammad Ali (JURNAL MANAJEMEN DAN BISNIS, 2025)
Purpose– This study aims to analyze the effect of green brand innovation on green brand loyalty with the mediating role of green perceived value. Novelty – This study contributes to the role of green perceived value as a mediator in the relationship between green brand innovation and green brand loyalty in the context of Islamic banking. Unlike previous studies that predominantly focused on the manufacturing sector and consumer products, this research specifically examines the Islamic banking industry in Indonesia, which is still rarely studied, even though this sector is strategic in promoting sustainable practices. Method – The study involved 165 active customers of Bank Syariah Indonesia in Yogyakarta, selected using a purposive sampling technique. The criteria for respondents included Bank Syariah Indonesia customers currently residing in Yogyakarta, customers who had used Bank Syariah Indonesia services for at least one year, and customers who had a good understanding of green brand innovation, green brand loyalty, and green perceived value. Data were collected through a questionnaire using a five-point Likert scale, measuring indicators of green brand innovation, green perceived value, and green brand loyalty adapted from prior studies. The data were analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS) with Smart PLS 4.0 Findings – The results of the study show that green brand innovation has a significant positive effect on green brand loyalty, green brand innovation has a significant positive effect on green perceived value, green perceived value has a significant positive effect on green brand loyalty, and green perceived value is proven to be a significant partial mediator in this relationship. Limitations and Implications – This research is limited to customers of Bank Syariah Indonesia in Yogyakarta, so generalization of the findings should be done cautiously. Nevertheless, these findings reinforce the relevance of Ajzen's (1991) theory of planned behavior concerning the role of positive attitudes and value perceptions toward green innovation in fostering the formation of intentions and consumer loyalty behavior. Practically, the results of this study can serve as a basis for Islamic banks in designing green innovation strategies focused on enhancing perceived green value to strengthen customer loyalty.